“SAYA KIRA SKI MEMBOSANKAN…”: NARASI SISWA MADRASAH ALIYAH DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM MELALUI PADLET - Angga Adi, Muryono (PAI RAFAH, 2024)
This research aims to thoroughly examine the experiences and perceptions of Madrasah Aliyah students in relation to their learning of Islamic Cultural History (SKI) through the collaborative online platform Padlet. The study adopts a qualitative approach with a narrative research design, utilizing semi-structured interviews to collect data from six student participants. The findings demonstrate a range of perspectives on the SKI learning experience both before and after the integration of Padlet in the classroom setting. In general, the integration of Padlet is deemed effective in enhancing students' learning experiences by incorporating engaging, participatory, and motivational elements, as well as fostering student creativity. Furthermore, the use of Padlet facilitates student collaboration, enabling the sharing of ideas and active participation in discussions. However, the study also identifies certain technical challenges that may arise when implementing Padlet in the learning context, such as limited internet access and difficulties faced by some students in utilizing the technology. The outcomes of this research are expected to make significant contributions to educators and researchers in their endeavors to continuously enhance the quality of history education, particularly in the context of SKI learning at Madrasah Aliyah. Additionally, the study emphasizes the importance of providing technical training and infrastructural support to maximize the benefits of modern educational technology. Future research could explore the long-term effects of using Padlet and similar platforms on student engagement and academic performance, as well as investigate strategies to overcome the identified technical barriers. This research also highlights the necessity for careful planning and support when incorporating such platforms to ensure that all students can fully reap the benefits of technological enhancements in their learning environments.